Implementasi sistem katalogisasi digital dalam meningkatkan efisiensi layanan perpustakaan sekolah - Taufiqurrahman, Muhammad; Ramli, Akhmad; Sudadi, Sudadi (Jurnal Madako Education, 2025)
From the understanding that OPAC is a catalog stored on a PC (digitized), so it can be accessed online and used to search for information about collections in the library. So that users can easily and quickly search for various book collections in the library. In conducting this research I used the Library research method (Literature Study) in searching for data and sources related to catalog digitization. Purpose and Function of OPAC There are several purposes for creating OPAC, including: Users can directly access the library database. Reduce costs and time spent by users to search for information. Reduce the workload of database management to improve work efficiency. Speed ​​up information searches. Able to meet the information needs of the community comprehensively. In the digital age, libraries are a place that must keep up with technological developments. Because libraries are places where people fulfill their information needs. To meet library information needs in the short term, libraries must have a catalog. Therefore, the tool of the current digitalization era, libraries must provide OPAC. OPAC is a computer catalog that can be used online and can be used to track information on library collections and other library information.